Revitalization of work oriented vocational education management system (Research, Society and Development, 2020)
The purpose of this study is to find out the model of vocational education revitalization that suits to the industry competency need and work oriented vocational education management system. The study was conducted in Jakarta, by exploring various policies related to efforts for revitalize vocational education. The findings of this study show that work oriented vocational education revitalization must be organized integratively. This allows for strengthening in curriculum, practice, testing and certification, which is directly connected to the demand for skills required by the business and industrial world. Theory content - practice are arranged according to on a dual system, where trainees follow theoretical learning program in school by 30% and practice and character education in workplace by 70%. Through this concept, it is possible for the business and industrial world to get the best workforce according to the need for qualification skills, more loyal, and more efficient.